1992
DOI: 10.1063/1.351041
|View full text |Cite
|
Sign up to set email alerts
|

Achievements and limitations in optimized GaAs films grown on Si by molecular-beam epitaxy

Abstract: A systematic study of the growth of high-quality films of GaAs on Si substrates has been performed for applications in devices, particularly in optoelectronic devices for cointegration in optical interconnects. The effort for optimized active layers was approached through the separate optimization of substrate preparation, growth time parameters, and postgrowth treatment. In particular, the study of growth involved the investigation of the effect of silicon substrate orientation, post-growth treatment, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Clearly, {110} oriented APBs are not conducive for self-annihilation. However, it has been observed experimentally with transmission electron microscopy (TEM) that while APBs in GaAs typically form along {110} planes they have a tendency to change their plane of propagation during growth [13][14][15][16][17]. Georgakilas et al, also analyzed the through-thickness APB density in a GaAs film grown on Si and found that the APB density decreased with increasing distance from the GaAs/Si interface, an indirect indication that the APBs were propagating along inclined planes and self-annihilating [17].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, {110} oriented APBs are not conducive for self-annihilation. However, it has been observed experimentally with transmission electron microscopy (TEM) that while APBs in GaAs typically form along {110} planes they have a tendency to change their plane of propagation during growth [13][14][15][16][17]. Georgakilas et al, also analyzed the through-thickness APB density in a GaAs film grown on Si and found that the APB density decreased with increasing distance from the GaAs/Si interface, an indirect indication that the APBs were propagating along inclined planes and self-annihilating [17].…”
Section: Introductionmentioning
confidence: 99%
“…The temperature at which a film nucleates determines the density and size of 3D nuclei. Lower temperatures ensure that many small GaAs islands coalesce, resulting in more efficient APD annihilation [30]. The subsequent growth at elevated temperature ensures that the material is highly crystalline.…”
Section: Discussionmentioning
confidence: 99%
“…The deposition of a nucleation layer at reduced temperature followed by a thick layer deposited at elevated temperature is a well-known technique for growing III-V materials on Si [5,6,[8][9][10]23,30,31]. The temperature at which a film nucleates determines the density and size of 3D nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The primary difficulty related to the association of GaAs and Si systems is the lattice mismatch of 4.1% between GaAs and Si, which results in high dislocation density (>10 8 cm À2 ) in the GaAs layers when directly grown on Si substrate [1]. Apart from the wafer bonding technique, several epitaxial approaches have been proposed and investigated to overcome this limitation, involving thick III-V buffers, thermal cycling, strained layers, and selective lateral overgrowth [2].…”
Section: Introductionmentioning
confidence: 99%